Detection of subclinical left ventricular dysfunction by global longitudinal strain imaging in diabetic and prediabetic patients and its correlation with high-sensitivity C-reactive protein and glycosylated hemoglobin - Nupur Goyal; Satyajit Singh; Amritava Ghosh; Surendra Kumar Naik; Abhishek Kumar; Amratansh Varshney; Nabodoy Majumder; Rounak Kumar (Heart India)
Background: Unlike conventional echocardiography, which primarily detects left ventricular (LV) diastolic dysfunction in diabetic cardiomyopathy, speckle tracking echocardiography (STE) can identify earlier, subclinical systolic dysfunction. Early STE detection may allow interventions to prevent heart failure progression. Objectives: The primary objective was to determine the prevalence of subclinical LV systolic dysfunction (measured by global longitudinal strain [GLS]) in diabetic and prediabetic patients with normal left ventricular ejection fraction (LVEF). The secondary objective was to correlate this dysfunction with high-sensitivity C-reactive protein (hs-CRP) and glycated hemoglobin (HbA1C). Materials and Methods: After screening and consent, diabetic/prediabetic outpatients underwent routine blood tests (lipid profile, HbA1c, thyroid, complete blood count, renal function, hs-CRP, microalbuminuria), Electrocardiogram (ECG), and echocardiography (GLS, tissue Doppler). GLS was correlated with hs-CRP and HbA1c using statistical methods. Results: GLS imaging revealed subclinical LV systolic dysfunction in 46.7% of subjects despite normal LVEF. This dysfunction was more prevalent in prediabetics (53.6%) compared to diabetics (46.4%). The mean HbA1c was 7.89 ± 2.29%, and the mean hs-CRP was 2.05 ± 1.05 mg/L. The correlation between GLS and hs-CRP, and HbA1c was not statistically significant. Conclusion: Previous research demonstrates that GLS imaging detects subclinical LV dysfunction in patients with normal LVEF, showing progressive strain changes despite stable LVEF. This supports GLS use for LV function assessment. Strain imaging can reveal preclinical systolic dysfunction before overt changes in the ventricular filling, identifying early myocardial impairment despite normal LVEF and diastolic function.